Electrochemical Activity and Electrical Properties of Optimized Polypyrrole Coatings on Iron. Issue 12 (1st January 2015) - Cysewska, Karolina; Virtanen, Sannakaisa; Jasiński, Piotr
Abstract : In this work, electrochemical activity and electrical properties of polypyrrole (PPy) coated iron electrodes have been investigated. PPy film was electrochemically polymerized from sodium salicylate aqueous solution under conditions, which provided an increase of iron corrosion resistance. It was noticed that the pH of the solution and the applied electrode potential range during the study of the polymer properties had an influence on the observed electroactivity of PPy. The electroactivity of PPy was retained in neutral solution when the potential was scanned between −0.6 and 0.3 V. Also the resistance behavior of the synthesized polymer film as a function of the electrode potential during doping/dedoping processes was studied. Determination of the resistance was based on the impedance spectroscopy measurements and was performed in air, in order to avoid the influence of the solution resistance on the resistance of the studied polymer. Depending on the redox properties, the pH of solution and the potential range, different resistances of the polymer film during the doping/dedoping process can be obtained.